Quantifying Uncertainty in Laser-Induced Damage Threshold for Cylindrical Gratings - Yuan Li; Junqi Xu; Guoliang Yang; Lihong Yang; Junhong Su (Micromachines)
The laser-induced damage threshold (LIDT) is a key measure of an optical component’s resistance to laser damage, making its accurate determination crucial. Following the ISO 21254 standards, we studied the measurement strategy and uncertainty fitting method for laser damage, establishing a calculation model for uncertainty. Research indicates that precise LIDT measurement can be achieved by using a small energy level difference and conducting multiple measurements. The LIDT values for the cylindrical grating are 15.34 ± 0.00052 J/cm2 (95% confidence) and 15.34 ± 0.00078 J/cm2 (99% confidence), demonstrating low uncertainty and reliable results. This strategy effectively measures the LIDT and uncertainty of various grating surface shapes, offering reliable data for assessing their anti-laser-damage performance.